The angiotensin-converting enzyme inhibitor, captopril, suppressed hepatic stellate cell activation via NF-kappaB or wnt3α/β-catenin pathway. Issue 1 (1st January 2021) - Gu, Zhaodi; Fang, Linjun; Ma, Peijun
ABSTRACT: Activation of hepatic stellate cells (HSC) is associated with hepatic fibrogenesis, which is one of complications of diabetes mellitus. Captopril possesses potent anti-inflammation, oxidative stress and fibrosis effects. However, the specific molecular mechanism of captopril in high glucose (HG)-induced hepatic stellate cells has not been elucidated. Following the treatment of HG or captopril treatment for rat hepatic stellate cells (HSC-T6), cell activities were detected by Cell Counting Kit-8 (CCK8) assay. Reactive oxygen species (ROS) levels were determined by ROS staining. The expression of inflammation-related proteins (Interleukin (IL)-1β, IL-6 and IL-8) and fibrosis-related proteins (fibronectin (FN), collagen I, collagen III, collagen IV, matrix metallopeptidase (MMP-2 and MMP-9) were determined by Western blot. Captopril significantly decreased HSC-T6 cell viability induced by HG in a dose-dependent manner, as well as decreased levels of malondialdehyde (MDA), ROS, pro-inflammatory markers and fibrosis-related proteins, while upregulated superoxide dismutase (SOD) activities. We further found that captopril decreased the ratio of p-IκBα/IκBα and the ratio of p-p65/p65. Intriguing, phorbol myristate acetate (PMA) or LiCl was able to significantly reverse the captopril-induced alteration of oxidative stress-, inflammation- and fibrosis-marker levels. In conclusion, in HG-stimulated HSC-T6 cells, captopril displayed a potent ability to inhibit oxidative stress, inflammation and hepatic fibrogenesis via NF-kappaB or wnt3α/β-catenin. These results demonstrated the mechanism of captopril as well as the role of the NF-kappaB or wnt3α/β-catenin on HSC-T6 activation induced by HG.